Metrical inequivalence in poetic translation - Toshpulatova , Dildora Ikromjon qizi (The Lingua Spectrum, 2026)
The article analyzes metrical dissonance in poetry translation using Yusuf Khass-Khаjib’s poem “Kutadgu Bilig” (11th century; one of the first monuments of Turkic writing). The study examines two English translations (W. May and R. Dankoff) and aims to identify inconsistencies in the prosodic structures of the original and the translations, classify the types of metrical transformations, and methods of conveying the rhythmic expressiveness of the text. A comparative analytical method is used, specifically comparing the poetic structure, rhythm, and stress in the original and translations. The theoretical section discusses approaches to poetic translation, in particular the concept of “functional equality” – the desire to achieve a similar poetic effect. The analysis reveals that, although May and Dankoff sought to harmonize meter and meaning during translation, their choice of meter differs. May relied more on iambic pentameter, thereby preserving the inherent musical rhythm of the aruz. Dankoff, on the other hand, used a semi-free tonic meter, ensuring a natural rhythm and intonational freedom.